Halal Medical Tourism: A Sentiment Analysis - Syahdatul Maulida; Lina Marlina (Halal Tourism and Pilgrimage, 2022)
This study aims to look at sentiments related to developments halal medical tourism in scientific publications published on the theme. This study uses a qualitative method with a sentiment analysis approach. The data used is secondary data with the theme â€œhalal medical tourismâ€ obtained from the Scopus database of 100 scientific publications. Data is processed using software SentiStrength for extracting and classifying sentiments. The results of the study found that positive sentiment was the highest with a percentage of 47%, followed by neutral sentiment with 36% and positive sentiment with a percentage of 17%. The increasing demand for halal trends, positive Muslim-friendly innovations and large business potential are reasons for positive sentiment. Meanwhile, there is no international sharia standard for providers medical tourism and related community literacy halal medical tourism still very low to be a negative issue.